1996
DOI: 10.1097/00003246-199606000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant replacement in the treatment of sepsis-induced adult respiratory distress syndrome in pigs

Abstract: We conclude that endotoxin caused lung injury typical of ARDS as demonstrated by pulmonary edema, an increase in PaCO2, and a decrease in PaO2, a decrease in static lung compliance and inhibition of surfactant function. Exogenous surfactant treatment effected only moderate improvements in lung function (i.e., reduced venous admixture and restored surfactant function) in this sepsis-induced ARDS model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
3
19
0
1
Order By: Relevance
“…Injury from oleic acid infusion via the pulmonary artery shows almost no improvement with surfactant, 150 although many would argue that this is a lethal injury with substantial cellular disruption 151 that is unlikely to respond to any therapy. A porcine sepsis model that used intravenous lipopolysaccharide infusion showed some oxygenation improvement following surfactant administration, 152,153 but the response was less striking than in the surfactant-treated animals injured with intratracheal lipopolysaccharide above. 146,147 It is notable that the different responses to surfactant between direct and indirect lung injury in animals resemble the response pattern seen in humans; analysis of 2 trials found that direct pulmonary ALI/ARDS is impacted most beneficially by surfactant therapy.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 96%
“…Injury from oleic acid infusion via the pulmonary artery shows almost no improvement with surfactant, 150 although many would argue that this is a lethal injury with substantial cellular disruption 151 that is unlikely to respond to any therapy. A porcine sepsis model that used intravenous lipopolysaccharide infusion showed some oxygenation improvement following surfactant administration, 152,153 but the response was less striking than in the surfactant-treated animals injured with intratracheal lipopolysaccharide above. 146,147 It is notable that the different responses to surfactant between direct and indirect lung injury in animals resemble the response pattern seen in humans; analysis of 2 trials found that direct pulmonary ALI/ARDS is impacted most beneficially by surfactant therapy.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 96%
“…in, such as Salmonella enteritidis [42] , are also used occasionally. In pigs and sheep, a dosage of 1-100 g/kg of LPS is diluted in normal saline and infused intravenously over a half hour to several hours [39][40][41][43][44][45][46][47] . In dogs, due to their tolerance to endotoxin, extremely high doses of endotoxin ( 1 1 mg/kg) are routinely needed to induce this model [48,49] .…”
Section: Oai Modelmentioning
confidence: 99%
“…Aspiration of acid [82][83][84]or meconium [85][86][87][88] Anti-lung serum infusion [89] Bacterial or endotoxin-induced injury [90][91][92][93][94][95] Bilateral vagotomy [96] Hyperoxic lung injury [97][98][99][100][101] In vivo lung lavage with mechanical ventilation [102][103][104][105][106][107] NNNMU-induced lung injury [108][109][110] Viral pneumonia [111,112] NNNMU is N-nitroso-N-methylurethane. See text for discussion.…”
Section: Summary and Future Prospects For Surfactant Therapy In Amentioning
confidence: 99%